Robin Hood, el proscrito - Donald, Angus, 1965- (Narrativas históricas Edhasa., 2010)
When he's caught stealing, young Alan Dale is forced to leave his family and go to live with a notorious band of outlaws in Sherwood Forest. Their leader is the infamous Robin Hood. A tough, bloodthirsty warrior, Robin is more feared than any man in the county. He becomes a mentor for Alan; with his fellow outlaws, Robin teaches Alan how to fight and how to win. But Robin is a ruthless man. Although he is Alan's protector, if Alan displeases him, he could also just as easily become his murderer.